Tax morale and fairness in conflict: An experiment - Christoph Engel; Luigi Mittone; Azzurra Morreale (Max Planck Institute for Research on Collective Goods, 2019)
Arguably, for many citizens the perceived expected disutility from sanctions is smaller than the monetary gain from tax evasion. Nevertheless most people pay their taxes most of the time. In a lab experiment, we show that the willingness to pay taxes even absent enforcement is indeed pronounced. Yet voluntary compliance is reduced if participants learn that income is heterogeneous. The effect is driven by participants with the lowest income. The reduction obtains irrespective of the tax regime. If the tax is proportional to income, or progressive, participants become more skeptical about the willingness of participants with high income to comply.
Keywords: C30; C91; D01; D02; D31; D63; D91; H26; K34; K42; 330; tax evasion; tax morale; heterogeneity; income inequality; lump sum tax; proportional tax; progressive tax; beliefs; path model